2015
DOI: 10.1242/jcs.160879
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of epithelial cell polarity by PAR-3 depends on Girdin transcription and Girdin–Gαi3 signaling

Abstract: Epithelial apicobasal polarity has fundamental roles in epithelial physiology and morphogenesis. The PAR complex, comprising PAR-3, PAR-6 and aPKC, is involved in determining cell polarity in various biological contexts, including in epithelial cells. However, it is not fully understood how the PAR complex induces apicobasal polarity. In this study, we show that PAR-3 regulates the protein expression of Girdin (GIV/CCDC88A), a guanine nucleotide exchange factor (GEF) for heterotrimeric Gαi subunits, at the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
54
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 82 publications
11
54
1
Order By: Relevance
“…Expression of GIV was significantly reduced (~by 80–85%) in Type II MDCK cells, which present 'leakier' junctions compared to Type I MDCK cells (Rothen-Rutishauser et al, 1998) (Figure 4—figure supplement 1). Such low levels of GIV expression have previously been reported by others [GIV in MDCK II cells could be detected by immunoblotting exclusively after enrichment by immunoprecipitation (Sasaki et al, 2015)]. Despite multiple attempts at depleting the residual low amounts of GIV by shRNA (lentiviral vectors), we failed to generate cell lines stably and reliably depleted of GIV, suggesting that the already low levels of endogenous GIV may be essential for the survival of MDCK cells in monolayer cultures.…”
Section: Resultssupporting
confidence: 46%
See 2 more Smart Citations
“…Expression of GIV was significantly reduced (~by 80–85%) in Type II MDCK cells, which present 'leakier' junctions compared to Type I MDCK cells (Rothen-Rutishauser et al, 1998) (Figure 4—figure supplement 1). Such low levels of GIV expression have previously been reported by others [GIV in MDCK II cells could be detected by immunoblotting exclusively after enrichment by immunoprecipitation (Sasaki et al, 2015)]. Despite multiple attempts at depleting the residual low amounts of GIV by shRNA (lentiviral vectors), we failed to generate cell lines stably and reliably depleted of GIV, suggesting that the already low levels of endogenous GIV may be essential for the survival of MDCK cells in monolayer cultures.…”
Section: Resultssupporting
confidence: 46%
“…GIV regulates epithelial cell polarity and morphogenesis (Bhandari et al, 2015; Houssin et al, 2015; Sasaki et al, 2015); it's role at cell-cell junctions has been attributed to its ability to bind PAR3 (Sasaki et al, 2015) and the cadherin-catenin complexes (Houssin et al, 2015), and accelerate nucleotide exchange on (i.e. activate) the trimeric G-protein α subunit, Gαi via its C-terminal GEF motif; Figure 1A (Sasaki et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, GIV-dependent signaling has been described at multiple intracellular compartments, including centrosomes, focal adhesions, cell-cell junctions, early endosomes, exocytic vesicles, autophagosomes, and more recently, on Golgi membranes [summarized in (8)]. The specific role of activation of G proteins by GIV has been investigated in the context of autophagy (19), secretory functions of the Golgi (50), and during the establishment of cell polarity (59), and these 3 studies have accomplished 3 key goals: 1) they prove that G proteins are active at internal locations; 2) that such activation can be brought on by cytosolic non-receptor GEF, GIV; and finally, 3) they provide valuable clues into how the same GEF, i.e., GIV may coordinate G protein signaling at the PM and on internal membranes. It is noteworthy that while all three aforementioned studies primarily investigated how GIV activates G proteins on intracellular locations, they also revealed the complexity and variation of the interactome at each location.…”
Section: Tyrosine-based G Protein Signaling: a New Paradigm Governed mentioning
confidence: 99%
“…For example, it has been reported that macromolecular complexes containing the PAR3 and PAR6 proteins play crucial roles in regulating apicobasal polarity, and relate nuclear movements migration in a variety of cellular systems (Solecki et al, 2004;Cadot et al, 2012;Sasaki et al, 2015). Interestingly, our immunocytochemical analyses of retinas of the four relevant GRF genotypes revealed that both PAR3 and PAR6 colocalize with β-catenin precisely at the OLM, the particular retinal layer marking the physiological limit for migration of cone photoreceptor nuclei in normal retinas that is also eventually trespassed by the abnormal ectopic nuclei frequently observed in GRF2-depleted retinas (Fig.…”
Section: Specific Detection Of Ectopic Nuclei In the Photoreceptor Sementioning
confidence: 99%